The Importance of Energy Security in Africa: A Case Study of Ghana, Nigeria, Burkina Faso, and Côte d’Ivoire - Eduah, Dominic Kwesi (Advances in Social Sciences Research Journal, 2025)
Using Ghana, Nigeria, Burkina Faso, and Côte d’Ivoire as four representative nations, this essay examines the vital role that energy security plays in Sub-Saharan Africa. These countries continue to struggle to provide sustainable, affordable, and dependable energy access—essential for national security, political stability, and economic growth—as global energy geopolitics changes. The study highlights the socio-economic impacts of energy insecurity, including disruptions to healthcare, education, agriculture, and industrial productivity, employing a cross-sectional methodology that incorporates structured questionnaires and interviews with selected communities and energy institutions. Nigeria and Burkina Faso still struggle with inconsistent supplies, ineffective systems, and a heavy reliance on fossil fuels and biomass, whereas Ghana and Côte d’Ivoire have made significant strides through sectoral reforms and infrastructure investments. To create resilient and inclusive energy systems in Africa, the paper emphasizes the close connection between energy security and broader development objectives, advocating for risk diversification strategies, regional integration, and investment in renewable energy sources.